Optimization of lithium separation conditions from Caspian seawater using fuzzy logic combined with dispersive liquid–liquid extraction. Issue 3 (4th May 2019) - Pourhassan Motlagh Sharemi, Romina; Rashidi, Abbas; Mallah, Mohammad Hassan; Safdari, Jaber
ABSTRACT: For optimization of separation conditions of lithium from the Caspian seawater, a new combination technique of liquid–liquid extraction and fuzzy logic is being used. In this research, disperser and extraction solvents, and ligand of benzo15-crown-5, have been quickly injected. It went to cloudy form solution contain small extraction solvent drops. The impact of different parameters such as the kind and concentration of benzo15-crown-5, the volume of disperser and extraction solvents, pH and extraction time have been optimized on the extraction percentage and analyzed using fuzzy logic. The effect of other metal ion on extraction percentage was also investigated. Under the optimized conditions (volume of tetrachloroethylene: 1.5 mL, volume of acetone: 120 mL, volume of benzo15-crown-5: 0.1 mL, concentration of benzo15-crown-5: 0.001 mol/L, and pH: 1), the extraction has increased to 74% for the synthesis sample and 31% for the real sample from Caspian seawater.